Qualitative Adversary Theory and its role in State and Society Fragmentation in Arab Region - Altaie, Abdelkader; Tarawneh, Sahar (Dirasat: Human and Social Sciences, 2021)
The study stems from the notion that human existence is governed by opposites conflicts theory.If this argument is politicized and applied it on Arab region, then we find that, due to its geostrategic value, it has always been a target for external forces policies that allied with internal forces sometimes for attainment In light of the above, the study tries to validate the hypothesis that conflicting interests represent basic conflicting adversaries that are difficult to reconcile, leading to a sustainable state of instability, and may lead to confrontations in which various power tools, including military force, are employed to achieve certain interests. Events experienced by Arab region, and still, are visions, aspirations and conflicting interests product ,which we have not found solutions to many of them so far, due to demands of the conflicting forces overlapping, either local, regional or international and in accordance with fragmentation and dismantling policies formulated by some Western departments and foreign decision-making centers